2014
DOI: 10.17824/huyuamd.60718
|View full text |Cite
|
Sign up to set email alerts
|

 23 Ekim 2011 Van (Doğu Anadolu) Depremi'nin (Mw=7.1) Sismotektonik Özellikleri

Abstract: ÖZ 23 Ekim 2011 Van depreminin geniş bant uzak-alan cisim dalga şekillerinin sonlu-fay modellemesi deprem kırılmasının ters faylanma olduğunu ve tek taraflı olarak GB'ya yayıldığını göstermiştir. Kırılma 5 km altında kısıtlı kalmış, yaklaşık 5.5 m en büyük kayma ile 25 x 16 km'lik bir fay alanını örtmüş ve yaklaşık 11 sn sürmüştür. Sonlu-fay modeli için hesaplanan sismik moment 4.6 x10 19 Nm (Mw=7.1) olup çoğunluğu kırılma başlangıcından sonraki 5-9 sn zaman aralığında serbestlenmiştir. Sonlu-fay analizi en bü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…2) and for the aftershocks of the 2011 Van earthquake ( Fig. 3; Table 3), Utkucu et al (2013b) Utkucu et al (2013b) resulted in virtually the same stress changes shown in Fig. 6a-b, suggesting moderate variations of the regional stress regime do not result in much change in the stress calculations.…”
Section: The Spatial Pattern Of the Aftershocks Versus The Mainshock mentioning
confidence: 69%
“…2) and for the aftershocks of the 2011 Van earthquake ( Fig. 3; Table 3), Utkucu et al (2013b) Utkucu et al (2013b) resulted in virtually the same stress changes shown in Fig. 6a-b, suggesting moderate variations of the regional stress regime do not result in much change in the stress calculations.…”
Section: The Spatial Pattern Of the Aftershocks Versus The Mainshock mentioning
confidence: 69%
“…GPS measurements reveal that the northern branch is more active than the other branches, with a fault slip rate of 22 ± 3 mm/yr) [33]. Sakarya and its vicinity, located between the Samanlı Mountains in the north and the Kocaeli peneplain, have been exposed to many earthquakes Ms ≥ 6.8 in both historical and instrumental periods due to this tectonic characteristic on the more active northern branch [34]. This activity can also be seen in the seismicity map of the last century (Figure 1).…”
Section: Geological and Tectonic Featuresmentioning
confidence: 98%
“…Consequently, 644 people lost their lives, 1966 were injured, and 252 were saved from the wreck. Besides, thousands of houses were destroyed or were damaged irreparably, causing thousands of people to lose their homes (AFAD, 2020a; Utkucu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%